CO2 switchable deep eutectic solvents for reversible emulsion phase separation. Issue 5 (21st December 2020) - Liu, Feijie; Xue, Zhimin; Lan, Xue; Liu, Zhenghui; Mu, Tiancheng
Abstract : CO2 switchable imidazole-based deep eutectic solvents (DESs) were formed and used for reversible phase separation of emulsions generated between DESs and oil. Abstract : The concept of CO2 switchable deep eutectic solvents (DESs) was proposed and a series of CO2 switchable imidazole-based deep eutectic solvents (DESs) was designed. The CO2 switch mechanism was investigated and the system was used for easy emulsion separation of olive oil from DESs. The benign CO2 switchable DESs have great potential applications in dissolution and easy separation.